Flooded credit markets: Physical climate risk and small business lending - Luca Barbaglia; Serena Fatica; Caterina Rho (European Commission, 2023)
We document that European banks charge higher interest rates on loans granted to small and medium-sized firms located in areas at high risk of flooding. At 6 basis points, the average risk premium does not adequately reflect the deterioration of loan performance in the aftermath of flood episodes, however. Firms in flooded counties are more likely to default on their loans than non-disaster firms. Floods reduce securitised credit in the local markets, suggesting that physical risks associated with climate change are borne within the banking sector.
Keywords: C55; G21; Q51; Q54; 330; climate change; loan default; loan pricing; natural disasters